Loading iron rails onto a flatcar near camp 6 at the White Pass summit during the construction of the White Pass & Yukon Railroad, Alaska, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Loading iron near camp 6 on W.P. & Y.R.R. Alaska" Original image in Hegg Album 3, page 30.